2020
DOI: 10.3390/microorganisms8071089
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella Phage LPST153 That Effectively Targets Most Prevalent Salmonella Serovars

Abstract: Foodborne diseases represent a major risk to public health worldwide. In this study, LPST153, a novel Salmonella lytic phage with halo (indicative of potential depolymerase activity) was isolated by employing Salmonella enterica serovar Typhimurium ATCC 13311 as the host and had excellent lytic potential against Salmonella. LPST153 is effectively able to lyse most prevalent tested serotypes of Salmonella, including S. Typhimurium, S. Enteritidis, S. Pullorum and S. Gallinarum. Morphological analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 77 publications
5
24
0
Order By: Relevance
“…This phage might directly degrade biofilms by killing bacteria during colonization onto the surface or it may act via an as yet unknown degradation mechanism. Previous studies similarly indicated that phages of the family Podoviridae not only inhibited bacterial growth but also decreased biofilm formation (36,61,62).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This phage might directly degrade biofilms by killing bacteria during colonization onto the surface or it may act via an as yet unknown degradation mechanism. Previous studies similarly indicated that phages of the family Podoviridae not only inhibited bacterial growth but also decreased biofilm formation (36,61,62).…”
Section: Discussionmentioning
confidence: 84%
“…No lytic activity was observed against the tested bacterial strains of normal intestinal flora. Different host ranges have been reported for Salmonella phages of the family Siphoviridae ( 35 , 36 ). A previous study indicated that Siphoviridae phages were considered as restricted-host-range bacteriophages ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported a broad host range lytic phage SAL-PG against S. gallinarum and S. pullorum with 77.77% infectivity ( Rahaman et al, 2014 ). In another study phage LPST153 was active against 5 tested strains of S. gallinarum , but showed lower EOP values ( Islam et al, 2020 ). The SGP-C was found spot negative against all tested strains of Pseudomonas aeruginosa , Klebsiella sp, Acinetobacter , and S. aureus , which agreed with the previously reported lytic phage LPST153 ( Islam et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…The study of the genome of phages is crucial today, but most investigations analyzed before to the last 10 years do not include the sequencing or annotation of these genomes. The complete genomes of phages are already included as a technique of characterization and phylogeny, but the in-depth analysis of these genomes has only been carried out very recently; this even allows us to discover new subfamilies and new genera of phages infecting food pathogens [43,125]. DNA genomes of Caudovirales range in size from about 15 up to 500 kbp [173].…”
Section: Morphology and Classificationmentioning
confidence: 99%